Digital Forensics : threatscape and best practices - Sammons, John; ScienceDirect eBooks (Waltham, MA : Syngress is an imprint of Elsevier, 2016)
This book surveys the problems and challenges confronting digital forensic professionals today, including massive data sets and everchanging technology. You will learn the basics of cryptocurrencies (like Bitcoin) and the artifacts they generate; discover why examination planning matters and how to do it effectively; incorporate behaviorial analysis into your digital forensics examinations; stay updated with the key artifacts created by the latest Mac OS, OS X 10.11, El Capitan. It discusses the threatscapes and challenges facing mobile device forensics, law enforcement, and legal cases; the power of applying electronic discovery workflows to digital forensics; shows the value of and impact of social media forensics. --
Multimedia and VoIP "streaming" appsCloud-based storage apps; Camera-enabled apps; Location data and apps; Geotagging and EXIF data within apps; Persistent threats and challenges -- what lies ahead for mobile device forensics; Data encryption and stronger passwords; "Burner" and Chinese phones; JTAG and Chipoff analysis -- advantages, challenges, and threats; Validation and best practices of mobile forensic tools and methods -- the forensic enigma; Conclusion; References; Chapter 6 -- Digital forensics in an eDiscovery world; Introduction; eDiscovery processes and EDRM; Cat or dog not mouse.
Online resource; title from digital title page (viewed on January 08, 2016).
Includes bibliographical references and indexes.
Elsevier
Keywords: Computer crimes -- Investigation; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Computer crimes -- Investigation; Electronic books